Metode Camels dan Islamicity Performance Index Pada Kesehatan Bank: Metode Camels dan Islamicity Performance Index Pada Kesehatan Bank - safarinda imani rinda; Mauizhotul Hasanah (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2021)
Bank Indonesia as the central bank needs a control over the banks to find out how the financial condition and business activities of each bank are by means of CAMELS measurements. CAMELS consists of a bank capital ratio (capital adequacy), earning asset quality ratio (asset quality), management ability to manage risk (management of risk), earning ability ratio (earning ability), liquidity ratio (liquidity sufficiency), and the ability to deal with market changes (sensitivity to market risk). The measurement of bank health is more focused on the financial aspects, and the regulations regarding bank health assessment apply to both conventional and Islamic banks. For conventional banks, the bank's soundness assessment is appropriate because conventional banks are profit oriented. For Islamic banks, the regulation on bank health assessment is not appropriate because the function of Islamic banks is not only profit oriented but also social oriented according to the mandate of Law no. 10 of 1998, and must be in accordance with the maqasid of sharia. Therefore it is necessary to look for alternative ways of assessing the health of Islamic banks that not only consider financial aspects but also accommodate social and sharia aspects. Soul, mind, descent, Mall that measures assets and the level of risk that will occur. Islamic banks also need to develop an index called the Islamicity Performance Index, so that the performance of Islamic financial institutions can really be measured starting from personal education, profit sharing, zakat ratios, and Islamic investment. This type of research used in this research is library research or library research.